PHYSICAL AND ORGANOLEPTIC CHARACTERISTICS OF MILK CARAMEL CANDY WITH DURIAN FRUIT (Durio zibethinus Murr) AND GERGA CITRUS (Citrus sp) JUICE - Endang Sulistyowati; Sigit Mujiharjo; Irnad Irnad; Agria Susanti; Siti Phatonah (BPFP Faperta UNIB, 2019)
This research aims to analyze the characteristics of milk caramel candy products including physical and organoleptic properties after the addition of durian and gerga orange fruit. This study used a complete randomized design (CRD) with 4 treatments and 4 replications namely P0: control, P1: 3% durian, P2: 6% durian, P3: 9% durian and G0: control, G1: 10% gerga orange fruit juice, G2 : 15% gerga orange fruit juice, G3: 20% gerga orange fruit juice. Variables measured included yield, density and organoleptic characteristics including color, aroma, taste, texture and tenderness. Organoleptic test showed that addition of durian fruit meat affect the texture and tenderness which showed significant differences (P <0.05); but had no significant effect (P> 0.05) on color, aroma, and taste. Addition of gerga orange fruit juice also had no significant difference (P> 0.05) organoleptic characteristic being tested. Based on preference, addition of durian fruit meat had a very significant effect (P <0.01) on the yield but had no significant effect (P> 0.05) on density. The addition of gerga orange fruit juice showed no significant effect (P> 0.05) on yield but gave a very significant effect (P <0.01) on density. Addition of durian fruit meat increased organoleptic characteristic; but addition of gerga orange fruit juice bring down the assessment of organoleptic tests on color, aroma, taste, texture and tenderness. Penelitian ini bertujuan untuk menganalisis karakteristik produk permen karamel susu meliputi sifat fisik dan organoleptik setelah adanya penambahan durian dan jeruk gerga. Penelitian ini menggunakan rancangan acak lengkap (RAL) 4 perlakuan dan 4 ulangan yaitu P0: kontrol, P1: 3% durian, P2: 6% durian, P3: 9% durian dan P0: kontrol, P1: 10% sari jeruk gerga, P2: 15% sari jeruk gerga, P3: 20% sari jeruk gerga. Variabel yang diukur yaitu sifat fisik (rendemen dan kerapatan) dan sifat organoleptik yang meliputi warna, aroma, rasa, tekstur dan keempukan. Hasil uji organoleptik menunjukkan bahwa penambahan daging buah durian mempengaruhi tekstur dan keempukan dengan perbedaan nyata (P<0,05) ; namun berpengaruh tidak nyata (P>0,05) terhadap warna, aroma, rasa. Penambahan sari jeruk gerga juga berpengaruh tidak nyata terhadap sifat organoleptik permen caramel susu. Berdasarkan modus kesukaan, penambahan daging buah durian berpengaruh sangat nyata (P<0,01) terhadap rendemen tetapi tidak memberikan pengaruh tidak nyata (P>0,05) terhadap kerapatan. Penambahan sari jeruk gerga berpengaruh tidak nyata (P>0,05) terhadap rendemen tetapi memberikan pengaruh sangat nyata (P<0,01) terhadap kerapatan. Penambahan daging buah durian meningkatkan sifat-sifat organoleptik yang diamati, dan penambahan sari jeruk gerga menurunkan penilaian organoleptik warna, aroma, rasa, tekstur dan keempukan.